PELATIHAN LITERASI LINGKUNGAN SISWA MELALUI RBL-STEM PADA GURU DALAM MENINGKATKAN KETRAMPILAN BERPIKIR KREATIF - Kristiana, Arika Indah; Ridlo, Zainur Rasyid; Dafik, Dafik; Thoyibah, Fifi; Yanuarsih, Elly; Murtini, Murtini; Safrida, Lela Nur (Jurnal Pengabdian Masyarakat Khatulistiwa, 2024)
ABSTRACTThe aim of this service is to provide training to teachers regarding students' environmental literacy which can be utilized in learning through RBL-STEM to improve teachers' creative skills.  The partner in this service is SMP Negeri 7 Jember. The method used is training related to material, students' environmental literacy, RBL-STEM, and the application of the school environment in learning. The outcome of this service is increasing teachers' creative thinking in the learning process.Keywords: RBL- STEM, students' environmental literacy, creative thinkingABSTRAKTujuan dari pengabdian ini adalah memberikan pelatihan kepada guru tentang literasi lingkungan siswa yang dapat dimanfaatkan dalam pembelajaran melalui RBL-STEM dalam meningkatkan ketrampilan kreatif guru.  Mitra dalam pengabdian ini adalah SMP Negeri 7 Jember. Metode yang dilakukan adalah pelatihan terkait materi, literasi lingkungan siswa, RBL-STEM, dan penerapan lingkungan sekolah dalam pembelajaran. Adapun outcome dalam pengabdian ini adalah peningkatan berpikir kreatif guru dalam proses pembelajaran. Keywords: RBL- STEM, students' environmental literacy, creative thinking